2021
DOI: 10.3389/fmicb.2021.662573
|View full text |Cite
|
Sign up to set email alerts
|

Infection by Diverse HIV-1 Subtypes Leads to Different Elevations in HERV-K Transcriptional Levels in Human T Cell Lines

Abstract: Human endogenous retroviruses (HERVs) make up ~8% of the human genome, and for millions of years, they have been subject to strict biological regulation. Many HERVs do not participate in normal physiological activities in the body. However, in some pathological conditions, they can be abnormally activated. For example, HIV infection can cause abnormal activation of HERVs, and under different infection conditions, HERV expression may be different. We observed significant differences in HERV-K transcription leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 64 publications
(101 reference statements)
0
14
1
Order By: Relevance
“…Surprisingly we were unable to reveal an impact of either HIV-1 or HIV-2 infection in HERV expression in CD4SP thymocytes using both CCR5-and CXCR4-tropic primary isolates. Although we did not exclude a possible later up-regulation of HERV expression, these results suggest a wired control of their expression in these mature quiescent thymocytes, in contrast with peripheral and activated CD4 T cells (18,20,35).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Surprisingly we were unable to reveal an impact of either HIV-1 or HIV-2 infection in HERV expression in CD4SP thymocytes using both CCR5-and CXCR4-tropic primary isolates. Although we did not exclude a possible later up-regulation of HERV expression, these results suggest a wired control of their expression in these mature quiescent thymocytes, in contrast with peripheral and activated CD4 T cells (18,20,35).…”
Section: Discussioncontrasting
confidence: 57%
“…Recent data from several cell types and tissues have also been highlighting host restriction factors that limit HERV expression (9), and the interplay with other viruses, including HIV and SARS-CoV-2 (7,(18)(19)(20)(21)(22). It is likely that the interplay between HERV expression and the activation of the cell-intrinsic pathways that detect cytoplasmic DNA and/or RNA may play a role in the response to viral infections, as well as in the human thymus, including possible modulation during cell selection (10).…”
Section: Introductionmentioning
confidence: 99%
“…Significantly high expressions of the HERV-K (HML-2) gag , env , and pol genes were detected in both moderate and severe COVID-19 patients. The gene expression of HERV-K (HML-2) is under the direct control of its long terminal repeats (LTRs), studies have shown that the HIV-1 tat gene can induce transcriptional activation of HERV-K(HML-2) LTR [ 65 , 66 , 67 ]. We speculate that the high expression of HERV-K (HML-2) gag , env , and pol genes in whole blood of COVID-19 patients may also be due to the similar activation of some specific SARS-CoV-2 genes, which increase the expression of the LTR region.…”
Section: Discussionmentioning
confidence: 99%
“…For each amplicon, cDNA samples were measured in triplicate. Primer sequences for amplification of HERV-K (HML-2) gag , pol , and env and β-actin were obtained from a previous study ( Li et al, 2021 ). These sequences were checked by the Primer Blast, Oligocalc, and Gene Runner programs.…”
Section: Methodsmentioning
confidence: 99%
“…The probe sets HERV-K (HML-2) env -C1, HERV-K (HML-2) pol -C2, or HERV-K (HML-2) gag -C3 (Advanced Cell Diagnostics, United States) consisted of 20 dual probes targeting different segments within the HERV-K (HML-2) env , HERV-K (HML-2) pol , or HERV-K (HML-2) gag . The standard sample was pretreated according to the manufacturer’s instructions and the previously reported literature ( Wang et al, 2012 ; Li et al, 2021 ). After the cells were treated, they were inoculated on culture slides.…”
Section: Methodsmentioning
confidence: 99%